The Contribution of Kipang Home Industry to Household Economy in Panyabungan - Siregar, Nurintan; Setiawati, Putri Citra (Economic: Journal Economic and Business, 2025)
This research explores the role of the kipang home industry in improving household income and promoting community empowerment in Panyabungan District, Mandailing Natal Regency. Using a qualitative descriptive approach, the study involved five kipang entrepreneurs as primary respondents. Data were collected through in-depth interviews and thematic analysis was conducted to derive key insights. The findings reveal that the kipang home industry significantly contributes to increasing household income, creating informal employment, and strengthening social solidarity within the community. Most of the business actors are women, indicating the potential for women's economic empowerment. Furthermore, this industry plays a role in preserving local culinary traditions while supporting the growth of micro, small, and medium enterprises (MSMEs). However, challenges such as limited access to capital, market reach, and business management skills remain. The study suggests the need for training, legal business registration, and digital transformation to enhance sustainability and competitiveness. Ultimately, the kipang home industry serves not only as an alternative economic source but also as a catalyst for inclusive and sustainable local development.